Coordination of Glucosinolate Biosynthesis and Turnover Under Different Nutrient Conditions - Jeschke, Verena; Weber, Konrad; Moore, Selina Sterup; Burow, Meike (Frontiers in Plant Science, 2019)
Dynamically changing environmental conditions promote a complex regulation of plant metabolism and balanced resource investments to development and defense. Plants of the Brassicales order constitutively allocate carbon, nitrogen, and sulfur to synthesize glucosinolates as their primary defense metabolites. Previous findings support a model in which steady-state levels of glucosinolates in intact tissues are determined by biosynthesis and turnover through a yet uncharacterized turnover pathway. To investigate glucosinolate turnover in the absence of tissue damage, we quantified exogenously applied allyl glucosinolate and endogenous glucosinolates under different nutrient conditions. Our data shows that, in seedlings of Arabidopsis thaliana accession Columbia 0, glucosinolate biosynthesis and turnover are coordinated according to nutrient availability. Whereas exogenous carbon sources had general quantitative effects on glucosinolate accumulation, sulfur or nitrogen limitation resulted in distinct changes in glucosinolate profiles, indicating that these macronutrients provide different regulatory inputs. Raphanusamic acid, a breakdown product that can potentially be formed from all glucosinolate structures appears not to reflect in planta turnover rates, but instead correlates with increased accumulation of endogenous glucosinolates. Thus, raphanusamic acid could represent a metabolic checkpoint that allows glucosinolate-producing plants to measure the flux through the biosynthetic and/or turnover pathways and thereby to dynamically adjust glucosinolate accumulation in response to internal and external signals.